Waste-to-energy and its asymmetric impact on ecological footprint: implications for environmental sustainability - Dzul Hadzwan, Husaini; Lean, Hooi Hooi; Amjad, Ali (Springer Nature, 2026)
As global populations grow and economies expand, the surge in municipal solid waste presents a significant challenge to ecological sustainability. Waste management involves a critical trade-off between traditional methods, such as landfilling and combustion, and the alternative of waste-to-energy (WtE) systems, which convert waste into usable energy. However, the environmental impact of these methods is not uniform, demonstrating an asymmetric effect depending on the strategy employed. This study investigates the asymmetric relationship between waste-to-energy and ecological footprints in China and the United States from 1980 to 2021, using advanced econometric techniques such as NARDL and MT-NARDL. Our findings highlight the potential of WtE systems in mitigating ecological footprints, offering a promising solution for sustainability in both countries. We recommend a dual-pronged strategy incorporating financial support to WtE plants alongside Feed-in Tariff (FIT) schemes. This will ensure their viability and foster an environment where these initiatives can thrive, ultimately contributing to a greener future.